Strategi Reaktivitas Tiktok Membangun Citra Merek Daihatsu PT Prima Parama Mobilindo - I Gusti Ayu Putri Wulandari; Sayu Kadek Jelantik; I Wayan Astraguna (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the reactivation strategy of the TikTok account as an effort by PT Prima Parama Mobilindo to build Daihatsu’s brand image in the digital era. The main issue addressed in this research stems from the company’s limited digital activity despite TikTok’s vast potential as a brand communication medium. The purpose of this study is to describe the strategy for reactivating the TikTok account, analyze the internal and external factors influencing its formulation, and explore the internal stakeholders’ perceptions of TikTok’s role in shaping Daihatsu’s brand image. A qualitative descriptive approach was employed, with data collected through non-participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted based on the theories of Brand Image, Integrated Marketing Communication, and Social Media Marketing. The findings reveal that the reactivation strategy focuses on producing creative and interactive content aligned with platform trends and collaborating with influencers. Internal factors such as limited human resources and technical capability pose major challenges, while external factors including the dynamics of social media trends and consumer behavior serve as key driving forces. The TikTok reactivation has been proven to strengthen Daihatsu’s image as a modern, friendly, and digitally adaptive brand.